Karyotypic and molecular identification of laboratory stocks of the South American fruit fly Anastrepha fraterculus (Wied) (Dipera: Tephritidae) - Basso, A; Sonvico, A; Quesada-Allue, L.A; Manso, F (Journal of economic entomology, 2003)
The taxonomic status of the tephritid pest Anastrepha fraterculus (Wied.) is a controversial subject, mainly because of misinterpretation of the observed genetic variation. In this work, the different karyotypes and DNA polymorphism of a geographically defined population from Northeastern Argentina were studied, using derived stocks maintained in the laboratory during 25 generations. The karyotypes were analyzed using C-banding and N-banding techniques, while DNA analysis was performed through the DNA polymerase chain reaction (PCR). The variants isolated from both the wild Montecarlo population and the derived laboratory stocks were fully compatible and are present in other wild populations from South Brazil (lat 31 degrees 30' S) to Mid-Argentina (lat 34 degrees 30' S). Single-pair crosses among stocks carrying different chromosomal variants demonstrated the absence of isolation barriers. The polymorphic fragments isolated by RAPDs/PCR showed polymorphisms among stocks whereas the analysis of rDNA ITS1 exhibit a unique ITS1 length. Our results seem to indicate that all the examined variants belong to a single species with extended polymorphism and therefore do not support the hypothesis that the extended chromosomal polymorphism in A. fraterculus implies the existence of a complex of cryptic species.